Socially responsible finance and investing : financial institutions, corporations, investors, and activists - Baker, H. Kent (Harold Kent), 1944-; Baker, H. Kent (Harold Kent), 1944-; Nofsinger, John R. (Hoboken, N.J. : John Wiley & Sons, 2012)
'A detailed look at the role of social responsibility in finance and investing. The concept of socially responsible finance and investing continues to grow, especially in the wake of one of the most devastating financial crises in history. This includes responsibility from the corporate side (corporate social responsibility) as well as the investor side (socially responsible investing) of the capital markets. Filled with in-depth insights and practical advice, Socially Responsible Finance and Investing offers an important basis of knowledge regarding both the theory and practice of this ever-evolving area of finance.As part of the Robert W. Kolb Series in Finance, this book showcases contributed chapters from professionals and academics with extensive expertise on this particular subject. It provides a comprehensive view of socially responsible foundations and their applications to finance and investing as determined by the current state of research. Discusses many important issues associated with socially responsible finance and investing, like moral hazard and the concept of'too big to fail' Contains contributed chapters from numerous thought-leaders in the field of finance Presents comprehensive coverage starting with the basics and bringing you through to cutting-edge, current theory and practice Now more than ever, we need to be mindful of the social responsibilities of all investment practices. The recent financial crisis and recession has changed the financial landscape for years to come and Socially Responsible Finance and Investing is a timely guide to help us navigate this difficult terrain'--Provided by publisher.
Peterson) -- Introduction -- In The Eye Of The Beholder: Controversial Credit Products -- A Palsy In The Invisible Hand: Distorted Consumer Finance Markets -- The Evolving Law Of Predatory Lending: A Brief Overview -- Predatory Warning Signs For The Socially Responsible Investor -- Summary And Conclusions -- Discussion Questions -- References -- About The Author -- Chapter 15 Use and Misuse of Financial Secrecy in Global Banking (Ingo Walter) -- Microeconomics of Financial Secrecy -- Summary And Conclusions -- Discussion Questons -- References -- About The Author -- Part III: Corporate Engagement -- Chapter 16 Corporate Social Responsibility and Corporate Governance (Lorenzo Sacconi) -- Introduction -- The Place Of Csr In The Corporate Governance Debate -- Summary And Conclusions -- Discussion Questions -- References -- About The Author -- Chapter 17 Measuring Responsibility to the Different Stakeholders (Amir Rubin and Eran Rubin) -- Introduction -- Measuring Social Performance -- Csr Components - The Different Stakeholders And Measures -- Summary And Conclusions -- Discussion Questions -- References -- About The Authors -- Chapter 18 Corporate Philanthropy (Janet Kiholm Smith) -- Introduction -- Evolving Views Of Corporate Philanthropy -- Corporate Philanthropic Practices -- Evidence On The Motivation And Impact Of Corporate Philanthropy -- The Impact Of Corporate Giving On Firm Performance -- Summary And Conclusions -- Discussion Questions -- References -- About The Author -- Chapter 19 Institutional Investor Activism (Diane Del Guercio and Hai Tran) -- Introduction -- How Institutional Investors Define Sri -- Shareholder Proxy Proposals As Activism.
Includes bibliographical references and index.
Keywords: Investments -- Moral and ethical aspects